Accompanying the development of emotion regulation - Hollerer, Luise (Psihološka obzorja (Ljubljana), 2022)
Emotion regulation is described as a milestone in a child’s emotional and social development. Various psychological studies have shown that children do differ in their development of expression, perception and regulation of their own emotions (Goleman, 2013; Petermann & Gust, 2016; Siegler et al., 2011) and explicit perceptual, language based and cognitive strategies to achieve regulative competences in early childhood. In accordance with international studies the results indicate the importance of enhancing the emotional development of children in kindergarten and at the beginning of school. Especially the role of socialconscious emotional regulation, anger management and inhibition of aversive external behavior seems to be a key element for learning engagement, school success, wellbeing and mental health. This requires professionals in pre- and primary school settings who are able to accompany children in and are capable to work on prevention and intervention in case children show externalizing behavior. The article focuses on the implementation of emotional learning and emotional regulation on a curricular basis for vocational training and discusses a multilevel and systemic approach for prevention.
Keywords: childhood development; curriculum; čustveni razvoj; education; emotional development; emotional regulation; kurikulum; prevention; preventiva; razvoj otroka; training; uravnavanje čustev; usposabljanje; vzgoja in izobraževanje